PERSONAL ADJUSTMENT AMONG ADOLESCENT: GENDER DIFFERENCE - Kumari, Bhavna; Kanti, Nishi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is aimed at finding the difference in personal adjustment in adolescents of Muzaffarpur district of Bihar. Hypothesis testing research design is adopted for this study. Data is collected from 100 male and 100 female adolescents using standardized questionnaire following convenience sampling technique. SPSS is used for data analysis. The results revealed that the present level of personal adjustment practices is just below the average among adolescents of Muzaffarpur district. The present level of home, health, social and emotional dimensions of personal adjustment practices is above the average among adolescents of Muzaffarpur district. Female reported higher personal adjustment than male in case of personal adjustment. It is also reported that female is significantly higher in case of home, health and social dimension of personal adjustment while no significant difference reported for emotional dimension among adolescents of Muzaffarpur district of Bihar. It is recommended to adolescents of Muzaffarpur district of Bihar to maintain the level and take help of psychiatric for further better level.